Температурная зависимость рабочих характеристик пьезоэлектрических сенсоров на основе поливинилиденфторида - Revenyuk, T. A.; Fedosov, S. N. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
It has been found that the piezoelectric sensors produced on the basis of electrified films of polyvinylidene fluoride (PVDF) work reliably in the temperature range from –20°C to +80°C. At the operating temperature of 80°C d33 piezocoefficient decreases by 2% during two years that is permissible. At higher temperatures irreversible reduction of the piezocoefficient was observed. The lowest temperature of the working range is close to the glass transition temperature of the amorphous phase of PVDF. Annealing of the films at 80°C ensures stabile characteristics of the sensors within a few years.